Pengaruh Pengetahuan Perpajakan, Sanksi Pajak, dan Persepsi Keadilan Terhadap Kepatuhan Wajib Pajak UMKM di Kota Malang - Istutik, Istutik; N Y, Amelia Aurel; Tuakia, Hedher (Assyarikah: Journal of Islamic Economic Business, 2024)
The large number of MSMEs, 66 million in Indonesia and 21 thousand in Malang City and the failure to achieve the tax revenue target are very interesting things to study and analyze the influence of tax knowledge, tax sanctions, and perceptions of justice on taxpayer compliance of MSMEs in Malang City. The number of samples used was 98 respondents of MSMEs in Malang City using a random technique based on area. Data collection through questionnaires, and multiple linear regression analysis was used using SPSS version 21.0 for Windows. The results of the study showed that the variables of taxation, tax sanctions, and perceptions of justice partially influenced taxpayer compliance of MSMEs. The coefficient of determination (Adjusted R square) value of 0.417 indicates that the variables of tax knowledge, tax sanctions, and perceptions of justice were able to contribute to the taxpayer compliance variable by 41.7%. Socialization of laws and regulations on taxes needs to be continuously carried out by local governments. Tax sanctions followed by perceptions of justice felt by taxpayers can help improve taxpayer compliance.